Humor sebagai Mekanisme Pertahanan Ego Tokoh Mamat dan Ujang dalam Novel Jurnal Risa: Mamat Ujang karya Risa Saraswati - Anggini, Dewi Salvika; Rokhmansyah, Alfian (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
Humor has evolved from mere entertainment into a therapeutic tool for alleviating psychological burdens. This study examines humor as an ego defense mechanism in Risa Saraswati's novel Jurnal Risa: Mamat Ujang, employing Sigmund Freud's psychoanalytic framework (id, ego, and superego). The research is driven by the rising prevalence of psychological disorders in society, while existing studies indicate humor's role in stress reduction though these findings require more robust empirical validation. The study aims to develop a theoretical framework for humor's self-defense function in the traumatic experiences of characters Mamat and Ujang, analyzing its role within Freud's personality structure and Morrison's humor theory. The methodology combines descriptive qualitative research with literary psychology. The study employs ten narrative excerpts and dialogues between the characters Mamat and Ujang, blending humor with traumatic experiences. Through close reading and interpretive analysis, it examines humor's role as an ego-defense mechanism and psychological regulator. The findings reveal distinct defense strategies in both characters when confronting inner conflicts. For both, humor serves to process negative emotions fear, shame, and guilt into laughter. The study concludes that ego-defense mechanisms are not limited to human characters but also manifest through ghost characters with unique psychodynamic functions. By framing humor as a defense mechanism for trauma processing, this research offers a fresh perspective on literary psychology.